2002
DOI: 10.1063/1.1504496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of helium ion implantation and annealing on the relaxation behavior of pseudomorphic Si1−xGex buffer layers on Si (100) substrates

Abstract: The influence of He implantation and annealing on the relaxation of Si 0.7 Ge 0.3 layers on Si ͑100͒ substrates is investigated. Proper choice of the implantation energy results in a narrow defect band Ϸ100 nm underneath the substrate/epilayer interface. During annealing at 700-1000°C, He-filled bubbles are created, which act as sources for misfit dislocations. Efficient annihilation of the threading dislocations is theoretically predicted, if a certain He bubble density with respect to the buffer layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 22 publications
0
38
2
Order By: Relevance
“…However, the He implanted sample shows an additional dechanneling peak (channel 480) due to the cavities formed at about 100 nm below the interface, which remain after the anneal. 10 Furthermore, we applied Si + ion implantation on an 88 nm thick Si 0.67 Ge 0.33 layer grown by MBE on a 100 nm SOI substrate. The sample was implanted with 150 keV Si + ions with a dose of 1 ϫ 10 14 cm −2 and annealed at 850°C for 600 s. Channeling investigations indicated, similar to Fig.…”
mentioning
confidence: 99%
“…However, the He implanted sample shows an additional dechanneling peak (channel 480) due to the cavities formed at about 100 nm below the interface, which remain after the anneal. 10 Furthermore, we applied Si + ion implantation on an 88 nm thick Si 0.67 Ge 0.33 layer grown by MBE on a 100 nm SOI substrate. The sample was implanted with 150 keV Si + ions with a dose of 1 ϫ 10 14 cm −2 and annealed at 850°C for 600 s. Channeling investigations indicated, similar to Fig.…”
mentioning
confidence: 99%
“…These cavities have special significance to capture the mobile impurities and structural defects which results in the reduction of strain. It has been reported that cavities can be used as an effective source of the strain relaxation of semiconductors hetrostructures [49]. Annealed samples presented enhanced strain relaxation in comparison to that of un-annealed ones, which is attributed to the capturing of defects by cavities during gettering process [50].…”
Section:  (Degrees)mentioning
confidence: 94%
“…Reduction of strain at the interface always leads to a lower defect density. Earlier results show [11,12] that He implantation through a pseudomorphic Si-Ge layer into Si substrates and subsequent annealing at 800 1C lead to complete strain relaxation and defect-free Si-Ge layers in comparison with un-implanted samples. He bubbles were formed in the annealed implanted Si.…”
Section: Introductionmentioning
confidence: 95%